Human Capital Management Analysis And Organizational Cultures For New Entrance In Ev Station Electric Vehicle Charging Station - Riski Ariani; Edi Hamdi (UniSadhuGuna Business School, 2023)
As the demand for electric vehicles increases, the industry has seen significant growth in EV charging infrastructure. One key element supporting EV Station success is effective human capital management and an organizational culture that aligns with business objectives. This research method is based on short-term, medium-term and long-term goals followed by conducting a 3-stage analysis, namely Input Stage, Matching Stage, Decision Stage, Porter's Generic Strategy and ending by creating a Lean Business Canvas. The results of this study are the employee's work experience, the expertise he has, the combination of work experience and expertise possessed by the employee such as technical expertise in terms of charging and equipment maintenance is an important foundation in employee selection and promotion. In addition, smart corporate strategies in human capital management also include incentives and reward programmes.